Morphological and Phylogenetic Evidences Reveal Four New Species of Cantharellus Subgenus Cantharellus (Hydnaceae, Cantharellales) From China - Zhang, Yu-Zhuo; Lin, Wen-Fei; Buyck, Bart; Liang, Zhi-Qun; Su, Ming-Sheng; Chen, Zuo-Hong; Zhang, Ping; Jiang, Shuai; An, Dong-Yu; Zeng, Nian-Kai (Frontiers in Microbiology, 2022)
The morphology and phylogenetic relationships of species of Cantharellus subgenus Cantharellus (Cantharellales, Hydnaceae) from China are investigated. Fourteen phylogenetic species were recognized in this subgenus for China including C. cibarius, C. hainanensis, C. laevihymeninus, C. macrocarpus, C. vaginatus, C. versicolor, C. yunnanensis, and four species newly described here as C. albopileatus, C. pinetorum, C. qiuweifanii, and C. ravus.